Video transcoding proxy for 3G wireless mobile Internet access. - Warabino, A.
Transcoding proxies for mobile World Wide Web access have been developed. In the near future, wideband mobile communication systems such as IMT-2000 will emerge, and these proxies will have to cope with a variety of media such as video. In this article we identify issues involved in viewing a video stream in a mobile computing environment; to handle these issues, we propose a video transcoding system and its control method. These mechanisms provide stable transmission of video data and comfortable video viewing on user clients by estimating the communication conditions, client device capabilities, and user preferences
Keywords: 3Gwireless mobile Internet access; IMT-2000.; Client device capabilities; Communication conditions; Control method; Mobile World Wide Web access; Mobile computing environment; Stable transmission; User clients; User preferences; Video stream; Video transcoding proxy; Wideband mobile communication systems